Status, challenges, and opportunities of mixed farming system in Bangladesh - Nasim, Muhammad; Ahmed, S.; Chowdhury, Dipok; Bhandari, Humnath (International Rice Research Institute, 2023)
About 85% of Bangladesh's land is plain land where the mixed farming system (MFS) is practiced in which crops and livestock, as major enterprises are integrated. The objectives of this study were to characterize Bangladesh's MFSs and identify their potential and problems at two representative locations in the country's north and south. Focus group discussions, key informant interviews, and field visits were used in the study. The results showed that the current MFSs were characterized by a mixture of subsistence and commercial farming and intensive and small-scale land ownership. Eighty-five percent of the land was used by crops and the remaining 15 percent was used for homestead production, which includes stables, poultry sheds and livestock raising areas, and vegetable and fruit trees. Small and marginal farmers made up most land-holding categories and with them, a significant number of landless farmers were noticed. MFS had several challenges, most of which can be overcome, and it also had further potential. The challenges included a lack of farmers’ understanding of MFS production processes, interaction, byproduct usage farmers’ skills, and so on. Farmers had limited ability to use technology. So, the conduction of location-specific on-farm technology generation and verification research and technology transfer assistance is important. Training support, technology demonstration, assistance from service providers, and on-farm farming system research are needed to obtain positive impacts.